A Novel microRNA of Japanese Flounder Regulates Antimicrobial Immunity Involving a Bacteria-Binding CSF3 - Li, Wenrui; Guan, Xiaolu; Sun, Bin; Sun, Li (Frontiers in Immunology, 2021)
MicroRNAs (miRNAs) are small non-coding RNAs that regulate diverse biological processes including immunity. In a previous high-throughput RNA sequencing study, a novel miRNA, pol-miR-novel_642, was identified from Japanese flounder (Paralichthys olivaceus), a farmed fish species with important economic value. In this study, we investigated the regulatory mechanism and the function of pol-miR-novel_642 and its target gene. We found that pol-miR-novel_642 targeted, in a sequence-specific manner, a flounder gene encoding an uncharacterized protein that is a structural homologue of murine granulocyte colony stimulating factor 3 (CSF3). The expression of pol-miR-novel_642 and its target gene (named PoCSF3-1) was regulated, in different manners, by the bacterial pathogen Edwardsiella tarda and the viral pathogen megalocytivirus. Overexpression of pol-miR-novel_642 or interference with PoCSF3-1 expression in flounder cells strongly potentiated E. tarda infection. Consistently, in vivo knockdown of PoCSF3-1 enhanced bacterial dissemination in flounder tissues but blocked viral replication, whereas in vivo overexpression of PoCSF3-1 inhibited bacterial dissemination and facilitated viral infection. Overexpression/knockdown of PoCSF3-1 and pol-miR-novel_642 also affected the activation of autophagy. Recombinant PoCSF3-1 (rPoCSF3-1) interacted with and inhibited the growth of Gram-negative bacteria in a manner that relied on a PoCSF3-1-characteristic structural motif that is absent in mouse CSF3. rPoCSF3-1 also regulated the proliferation, inflammatory response, and immune defense of flounder head kidney leukocytes in a structure-dependent fashion. Together, these results reveal the function of a novel miRNA-CSF3 regulatory system of flounder, and add new insights into the role and mechanism of fish miRNA and CSF3 in antimicrobial immunity.